Minat Generasi Muda Terhadap Sektor Pertanian: Young Generation Interest in Agricultural Sectors - Roidah, Ida Syamsu; Laily, Dona Wahyuning; Prasekti, Yuniar Hajar (Jurnal Ilmiah Manajemen Agribisnis, 2024)
The agricultural sector in Indonesia plays an important role in supporting the national economy through its contribution to Gross Domestic Product (GDP), employment, and poverty reduction, especially in rural areas. However, this sector faces challenges such as low interest of the younger generation to be involved in agriculture, due to low income levels, limited access to modern technology, and negative perceptions of the sector. This study aims to identify factors that influence the interest of the younger generation in the agricultural sector using the binary logistic regression method. Data were collected from 40 young farmers in Ngraho District, Bojonegoro Regency, who were selected using purposive sampling. The analysis shows that the variables of need, awareness, family environment, and community environment have a significant influence on the interest of the younger generation to work in the agricultural sector. In contrast, the variables of interest and pride do not have a significant influence. These results indicate the importance of policies that support increasing farmer incomes, introducing modern technology, and educational programs to increase awareness and attractiveness of the agricultural sector among the younger generation. This study highlights the need for transformation of the agricultural sector into a modern agro-industry to encourage sustainability and inclusiveeconomic development.